Study on Meconium stained fluid-perinatal outcome - Harikumar, Soumya; Rajesh, Aparna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of this study is to find a correlation between the presence of MSAF in mothers with co- morbidities like PIH and GDM and to study the fetal heart variability in cases with MSAF and the significance of an admission test. This study also throws a light on the perinatal outcomes associated with MSAF. Methods: 100 women in labor with Meconium stained amniotic fluid were taken in this study. An admission test was done for all patients, along with continuous fetal heart monitoring was done in the presence of MSAF. Effect of thin and thick meconium on fetus was studied. The cases with maternal co-morbidities were closely monitored along with the mode of delivery, Apgar score, birth weight, resuscitation of baby was studied. All the newborns born through meconium stained liquor were followed up to one week of neonatal life. Results: Out of a total of 100 cases there was 60 cases with thick meconium with a non-reactive NST seen in 65% cases with thick MSAF and 32.5% cases with thin MSAF. 79% of cases with MSAF underwent emergency LSCS. The neonatal complications were more with thick meconium stained liquor accounting to 28.3% incidence of MAS, 23.3% of sepsis, 3.3%of pneumonitis and 21.7% of birth asphyxia. Conclusions: This study ascertained the need for an admission test and continuous CTG monitoring in cases detected to have meconium stained amniotic fluid. Co-morbidities like GDM did have a small role to play though the incidence was not very high. The neonatal complications were more common among cases with thick meconium stained liquor and probably the use of procedures like amnioinfusion can bring down the incidence of perinatal morbidity along with the rate of caesarean sections.